Development and Creation of Gas-Sensor System Based on Low Dimensional Metal Oxides - Bovhyra, R.V.; Zhyrovetskyy, V.M.; Popovych, D.I.; Savka, S.S.; Serednytskij, A.S. (Science and Innovation, 2024)
Peculiarities of photoluminescent properties of metal oxide nanopowders (ZnO, TiO2 , SnO2, WO3) including laser-modified and surface doped by impurities (Au, Ag, Pt, Ni, Cu, Sn), in gases (О2 , N2 , H2 , CO, CO2) have been studied. The sensor properties of the metal oxide nanopowders (adsorption capacity, speed, sensitivity, selectivity) have been established; the best structure and materials for the development of a multicomponent recording matrix have been selected. The efficiency of the sensor system for detection and analysis of gases and their mixtures has been found. The developed gas sensor system enables detecting not only separate gas components, but their mixture with high sensitivity and selectivity, which makes it possible to reach the advanced level of the formation of gas sensor systems with improved performance.